1999
DOI: 10.1091/mbc.10.5.1581
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of an Insulin-responsive Vesicular Cargo Compartment Is an Early Event in 3T3-L1 Adipocyte Differentiation

Abstract: Differentiating 3T3-L1 cells exhibit a dramatic increase in the rate of insulin-stimulated glucose transport during their conversion from proliferating fibroblasts to nonproliferating adipocytes. On day 3 of 3T3-L1 cell differentiation, basal glucose transport and cell surface transferrin binding are markedly diminished. This occurs concomitant with the formation of a distinct insulin-responsive vesicular pool of intracellular glucose transporter 1 (GLUT1) and transferrin receptors as assessed by sucrose veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
70
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 70 publications
12
70
0
Order By: Relevance
“…This observation is consistent with other studies in 3T3-L1 cells (El-Jack et al, 1999;Gross et al, 2004) in transition from preadipocyte to adipocyte morphology. Interestingly, in the present study no insulin effect on total cellular GLUT-4 expression was observed as might have been expected; although it may be assumed that GLUT-4 would be recruited to the plasma membrane in response to insulin.…”
Section: Discussionsupporting
confidence: 94%
“…This observation is consistent with other studies in 3T3-L1 cells (El-Jack et al, 1999;Gross et al, 2004) in transition from preadipocyte to adipocyte morphology. Interestingly, in the present study no insulin effect on total cellular GLUT-4 expression was observed as might have been expected; although it may be assumed that GLUT-4 would be recruited to the plasma membrane in response to insulin.…”
Section: Discussionsupporting
confidence: 94%
“…Importantly and as cited in the introduction, IRAP was also identified in this way as marker for GSV trafficking that is apparently more abundant than GLUT4 itself. Indeed, we have shown that IRAP is directed to GSVs during the course of 3T3-L1 adipocyte differentiation before significant GLUT4 expression occurs (El-Jack et al, 1999). Moreover, in engineered adipocytes, IRAP can become essentially the only major cargo constituent of GSVs and it responds to insulin in a manner similar or identical to GSVs from 3T3-L1 cells (Gross et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…Efforts to further understand this phenomenon are underway. The development of GSVs occurs during the differentiation of adipocytes, presumably as a result of the expression of an as yet unknown protein or proteins that initially results in the sequestration of IRAP, then GLUT4 (El-Jack et al, 1999). It is unlikely that p115 is one of these putative proteins as its expression is unchanged over the 8 -10 d required for adipocytes to fully differentiate (unpublished data)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations